(untitled) (Journal of Economics and Management Research, 2021)
تهدف هذه الدراسة الى التحليل استقرار صناعة الخدمات المالية الاسلامية خلال الفترة 2017-2018 وكذلك تحديد التحديات التي تواجه استقرارها ، و لتحقيق أهداف الدراسة تم استعمال بيانات تقارير مجلس الخدمات المالية الإسلامية 2018-2019. وقد خلصت الدراسة أن صناعة الخدمات المالية الإسلامية العالمية حققت مسار نمو ايجابي في الأصول و الموجودات ، غير أن استقرارها يتحدد بعدة تحديات الداخلية منها والخارجية This study aims to analyze the stability of the Islamic financial services industry during the period 2017-2018, as well as identify the challenges facing its stability, and to achieve the objectives of the study, the data of the Islamic Financial Services Board 2018-2019 reports were used. The study concluded that the global Islamic financial services industry has achieved a positive growth path in assets, but its stability is determined by several internal and external challenges.